Use of erectile dysfunction treatments after prostate cancer treatment and their perceived impact on men’s sex life: an analysis of patient reported outcome survey data - Megan Charlick; Tenaw Tiruye; Kerry Ettridge; Michael O’Callaghan; Alex Jay; Kerri Beckmann (BMC Urology)
Abstract Background Although sexual dysfunction is a common treatment side-effect affecting men’s quality of life, many prostate cancer patients do not receive or seek out treatments for erectile dysfunction (ED). The aims of this study are to investigate the extent and patterns of use of ED treatments and their perceived impact at different times following prostate cancer treatment. Methods This retrospective cohort study included all men on the South Australian prostate cancer registry who completed one or more Patient Reported Outcome Measures (PROMs) survey from 2016 to 2023 (n = 5561). Outcomes included self-reported use of ED treatment (oral medications, intra-cavernosal injections (ICI) and vacuum pumps) and their impact men’s sex life at various time points after treatment. The type and timing of ED treatments used was analysed descriptively. Sociodemographic and clinical characteristics associated with utilisation and self-reported satisfaction were examined using multivariable mixed-effects binomial logistic regression. Results Post-treatment use of ED treatments did not exceed 43% at any timepoint, with utilisation rates decreasing over time. Oral medications were most frequently used, while vacuum pump and ICI use was limited. Oral medications were more likely to be used at three-months (odds ratio [OR] = 2.48; 95% confidence interval [95%CI] = 1.88–3.27) and six-months (OR = 2.10; 95%CI = 1.63–2.27) than at 12-months post-treatment, and among men from higher socioeconomic areas (OR = 2.41; 95%CI = 1.47–3.93, highest vs. lowest quintile), and following prostatectomy (OR = 4.37; 95%CI = 2.92–6.42), and less likely among older men (OR = 0.08; 95%CI = 0.05–0.13, < 60yrs vs. 70-79yrs). Men were more likely to report an improved sex life with oral medication use at two-years (OR = 3.79; 95%CI = 1.69–8.47) and five-years (OR = 3.07; 95%CI = 1.51–6.25) post-treatment compared with 12-months or if they were socioeconomically advantaged (OR = 3.22; 95%CI = 1.30–7.96, highest vs. lowest quintile). Conclusions A substantial proportion of Australian men do not access or continue to use ED treatments after prostate cancer treatment, with many users reporting only modest effects on their sex life. There is a need to improve access to and maintenance of ED treatments following prostate cancer treatment.